2020
DOI: 10.1177/2158244020938702
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Project-Based Learning (PBL) Approach as a Way to Engage Students in Learning

Abstract: The prevalence of project-based learning (PBL) has increased significantly, contributing to serious discussions about its advent. PBL’s critics doubt whether accentuating the practice supports teachers in using a technocratic method in education, instead of promoting instruction that is responsive to students’ ideas. Thus, this study aims to develop on using the effectiveness of the PBL approach, as a way to engage students in learning as well as to incorporate literature on the PBL method for educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
121
0
22

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(226 citation statements)
references
References 70 publications
(94 reference statements)
5
121
0
22
Order By: Relevance
“…Additionally, Siron et al (2020) focused on the perception of adopting technology in the learning process, while Cerezo et al (2020) concerned with self-regulated learning for students during the pandemic. The major scholars have demonstrated that problem-based learning, project-based learning, as an attempt to achieve learning goals (Chang et al, 2020;Pohan et al, 2020;Almulla, 2020). However, game-based learning for economics has been overlooked by scholars.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Siron et al (2020) focused on the perception of adopting technology in the learning process, while Cerezo et al (2020) concerned with self-regulated learning for students during the pandemic. The major scholars have demonstrated that problem-based learning, project-based learning, as an attempt to achieve learning goals (Chang et al, 2020;Pohan et al, 2020;Almulla, 2020). However, game-based learning for economics has been overlooked by scholars.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have proposed various methods or approaches to improve student engagement through collaborative learning using a different approach (Chen & Chiu, 2016;Zheng, Zhang & Gyasi, 2019;Sanz-Martínez, Martínez-Monés, Dimitriadis & Bote-Lorenzo, 2019;Oluwajana & Adeshola, 2021). Some researchers have investigated a project-based learning method on collaborative learning (O'Sullivan, Krewer & Frankl, 2017;Almulla, 2020), wiki-supported collaborative learning for students' engagement (Yusop & Basar, 2017). However, most of the prior studies focus on teachers' role in promoting students' engagement in collaborative learning, ignoring other group members' roles.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is considered to be one of the most suitable pedagogical tools for the development of students' marketing competencies. This approach is characterized by the creation of student research teams that work on long-term projects (usually one or two semesters) connected to real world business practice with the purpose of solving the actual business tasks and problems [23,24].…”
Section: Introductionmentioning
confidence: 99%